Market segment evaluation and selection based on application of fuzzy AHP and COPRAS-G methods - Aghdaie, Mohammad Hasan; Zolfani, Sarfaraz Hashemkhani; Zavadskas, Edmundas Kazimieras (Journal of Business Economics and Management, 2013)
Market segment evaluation and selection is one of the critical marketing problems of all companies. This paper presents a novel approach which integrates fuzzy analytic hierarchy process (FAHP) and COPRAS-G method for market segment evaluation and selection. Fuzzy AHP is used to calculate the weight of each criterion, and COPRAS-G method is proposed to prioritize market segments from the best to the worst ones. The application of fuzzy set theory allows incorporating the vague and imprecise linguistic terms into the decision process. This study can be used as a pattern for market segment selection and future researches. A case study on a chair manufacturing company is put forward to illustrate the performance of the proposed methodology.First published online: 14 Sep 2012